Early scientific research training links to the innovation ability of medical undergraduates and postgraduates - Wang, Boyang; Yang, Lulu; Gong, Zhaohui (Frontiers in Education, 2024)
Scientific research training (SRT) is crucial for fostering skills and innovation in college students. However, the status of SRT in medical undergraduates and postgraduates, as well as the impact of early SRT on students’ innovation abilities, remain largely unknown. This study assessed the role of SRT in culturing innovation abilities among medical students. The results revealed that undergraduates exhibited a greater understanding of scientific research compared to postgraduates. Notably, undergraduates demonstrated a higher level of understanding of SRT in contrast to postgraduates (81.26% vs. 56.97%). A significant proportion (>70%) of undergraduates had engaged in research activities early in their academic journey, with an average participation duration exceeding 1 year. Moreover, undergraduates initiated their involvement in SRT during the first- and second- year of undergraduates, which was earlier than postgraduates. Personal interest emerged as a primary motivator for engaging in SRT, with postgraduates exhibiting higher research aspirations and achieving greater research outcomes. Postgraduates also received more substantial guidance from advisors, leading to enhanced academic performance compared to undergraduates (90.7% vs. 67.59%). Interestingly, students expressed satisfaction with laboratory conditions and attributed their academic success to personal efforts. These findings underscore the importance of early SRT in cultivating the innovation abilities of medical students.